Pyramid Energy Therapy in Oncology: A Quantum Bioenergetic Approach to Cancer Healing (Global Journal of Medical Research, 2025)
Cancer remains one of the most formidable challenges in modern medicine, prompting continuous exploration of innovative and integrative therapeutic approaches. This study investigates the potential of pyramid energy-a concept rooted in ancient architectural principles and emerging quantum bioenergetic theories-as a complementary modality in oncology. Drawing from interdisciplinary perspectives in physics, biology, and energy medicine, we explore how the geometrical properties of pyramids may influence cellular behavior, promote energetic alignment, and facilitate biological repair processes. A review of historical accounts, anecdotal reports, and preliminary experimental data suggests that the unique electromagnetic environment within pyramid structures may exert subtle but measurable effects on living cells, particularly in modulating oxidative stress, enhancing mitochondrial function, and supporting immune response. While current evidence remains largely theoretical or exploratory, the integration of pyramid energy principles into oncology may open promising avenues for noninvasive, low-risk adjunct therapies. This paper calls for more rigorous, controlled clinical studies to validate these effects and establish a scientific framework for their application in cancer care.
Keywords: pyramid energy; cancer therapy; bioenergetics; quantum healing; electromagnetic fields; integrative oncology; non-invasive treatment